2010
DOI: 10.1136/qshc.2009.035121
|View full text |Cite
|
Sign up to set email alerts
|

Medication reconciliation in the emergency department: opportunities for workflow redesign

Abstract: Ideas for an optimal workflow to generate a medication list include involving patients and utilising clerical staff to a greater extent in medication information gathering, identifying and flagging patients with missing medication information, and gathering only the medication information needed to make clinical decisions in the emergency department.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 19 publications
(10 reference statements)
0
26
0
Order By: Relevance
“…However, application of HLM stimulates discussion about how to solve system and process issues and improve quality and patient safety 22,60,68,74. Most of the analyzed papers have underscored the limits of HLM and barriers to its implementation,9,21,31,32,39,52,54,56,57,60,62,63,65,66,68,78 demonstrating that HLM can not be successfully implemented without considering the proper critical factors and precautions highlighted in the previous section of this paper.…”
Section: Resultsmentioning
confidence: 99%
“…However, application of HLM stimulates discussion about how to solve system and process issues and improve quality and patient safety 22,60,68,74. Most of the analyzed papers have underscored the limits of HLM and barriers to its implementation,9,21,31,32,39,52,54,56,57,60,62,63,65,66,68,78 demonstrating that HLM can not be successfully implemented without considering the proper critical factors and precautions highlighted in the previous section of this paper.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it was found that implementation of the eMedRec tool had a significant impact on improving compliance 31 32. Meanwhile, one study demonstrated that increased participation of patients and clerical staff in the generation of medication lists can improve the MedRec process 33. Whether the workflow can function to facilitate or increase the compliance of MedRec remains unknown, due to a lack of more evidence.…”
Section: Discussionmentioning
confidence: 99%
“…18 Until now, only one study has used a process mapping technique to address MedRec. An evaluation of four community hospital EDs in Washington identified common problems that inhibited high-quality and efficient MedRec, which led to the development of an improved workflow 19. However, the process mapping was only done in focus groups, so represented what clinicians believed to happen, rather than what was actually observed to happen.…”
Section: Introductionmentioning
confidence: 99%